2007
DOI: 10.1097/01.hp.0000261600.29366.b4
|View full text |Cite
|
Sign up to set email alerts
|

The Estimation of the Number of Underground Coal Miners and the Annual Dose to Coal Miners in China

Abstract: This paper introduces an estimation method for the number of underground coal miners and the annual dose to coal miners in China. It shows that there are about 6 million underground miners at present and the proportion is about 1, 1 and 4 million for national key coal mines, state-owned local coal mines, and township and private-ownership coal mines, respectively. The collective dose is about 1.65 x 10(4) person-Sv y(-1), of which township and private-ownership coal mines contribute about 91%. This paper also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…The estimated number of underground miners at present is about 6 million 20) . Although the prevalence of CWP should decrease dramatically in China 21) , the sheer number of 6 million coal miners still makes it a challenge to effectively prevent it and cure it or its complication.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated number of underground miners at present is about 6 million 20) . Although the prevalence of CWP should decrease dramatically in China 21) , the sheer number of 6 million coal miners still makes it a challenge to effectively prevent it and cure it or its complication.…”
Section: Discussionmentioning
confidence: 99%
“…In some coal mines in China, however, the uranium content of the coal seams is relatively high and the mines are ventilation-poor, which leads to the potential risk of radon accumulation and radiological impacts on miners. Liu et al [11] measured radon concentrations in 48 coal mines in twelve major coal-producing provinces in China. The results showed that there were greater radon concentrations in stone-coal mines without auxiliary ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are about six million underground coal miners in China [26]. Most of them often have to face high job demands, low social status, workplace discrimination, strict safety regulations, irregular life, and work-life interference, which are likely to negatively impact their mental health [27, 28].…”
Section: Introductionmentioning
confidence: 99%